Regulatory Limits of Empowering Biogas Digester Integrated with Indonesia’s Local Wisdom - Listiningrum, Prischa; Maheswara, Ida Bagus Ayodya; Wahyuni, Herlin Sri; Vibhu, Avanish (Lentera Hukum, 2023)
This paper analyses the international and domestic regulatory framework for managing waste-to-energy in Indonesia’s rural areas to support climate mitigation. The countryside is known to be the most significant contributor to organic waste due to the high productivity of the agricultural and livestock sectors. In contrast, organic waste is left without proper management and contributes to global greenhouse gas emissions. Indonesia has agreed to contribute to the Paris Agreement to reduce emissions by 29% in 2030 or 41% with international assistance, but its follow-up to switch to renewable energy appears insufficient. This study uses a socio-legal approach to unpack the waste-to-energy problems in one of Indonesia's villages: Tawangsari Village, Pujon District, Malang Regency, East Java Province. The study results reveal that the biogas program launched by the government through the "Program BIRU" was not aligned with local conditions in Tawangsari Village because not all farmer households had sufficient land to build a fixed dome. Thus, it is necessary to build a community-based centralized biogas digester. However, there are no provisions in the regulations governing the mechanism for funding renewable energy development in villages, as mandated by Article 20(2) of the Energy Law. The village can use village funds to carry out development based on local wisdom, but the limited number of village funds causes limited growth. There are no standard rules for bio-slurry processing and maintenance of biogas digesters to ensure the sustainability management of biogas. This paper recommends enacting national and/or domestic regulations to support the energy-independent village program, aligning with the government's commitments to reduce global emissions from the agricultural and waste sectors.Keywords: Climate Mitigation, Energy Transition, Regulations, Small-Scale Biogas.